2000
DOI: 10.1111/j.1528-1157.2000.tb01558.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pilocarpine‐Induced Status Epilepticus in Developing Rats: A Long‐Term Behavioral and Electrophysiological Study

Abstract: Summary:Purpose: Animal models are useful for the study of status epilepticus (SE)-induced epileptogenesis and neurological sequelae, especially during early brain development. Here, we show several permanent abnormalities in animals subjected to multiple SE during early development.Methods: Wistar pup rats (7 to 9 days old) were subjected to three consecutive episodes of SE induced by systemic pilocarpine injections. To study the long-lasting consequences of early-induced SE, chronic electroencephalographic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 33 publications
6
27
0
Order By: Relevance
“…These changes could underlie the behavioral deficits and generalized epileptic discharges observed in adulthood (15,16). The most prominent changes observed were (a) altered intracortical microcircuitry development; (b) anticipated PV immunoreactivity in neocortical interneurons; (c) increased GAD-65 immunoreactivity; and (d) altered neocortical apoptotic process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes could underlie the behavioral deficits and generalized epileptic discharges observed in adulthood (15,16). The most prominent changes observed were (a) altered intracortical microcircuitry development; (b) anticipated PV immunoreactivity in neocortical interneurons; (c) increased GAD-65 immunoreactivity; and (d) altered neocortical apoptotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Despite hippocampal resistance to neuronal Address correspondence and reprint requests to Dr. A. V. Silva at Lab Neurologia Experimental UNIFESP-EPM, Rua Botucatú, 862, CEP 04023-900 São Paulo, SP, Brazil. E-mail: valotta.nexp@epm.br damage during early development, Santos and colleagues (15,16) recently demonstrated that multiple episodes of pilocarpine-induced status epilepticus (SE) in developing rats (P7-P9) led to progressive neocortical/hippocampal epileptiform activity, persistent in vitro hyperexcitability, increased hippocampal/thalamic apoptosis, and severe cognitive impairment in adulthood.In contrast to adult rats that develop hippocampal damage and complex partial seizures (17), developing rats treated at P7-9 develop generalized electrographic seizures without marked hippocampal damage (15,16). These findings suggest a diffuse involvement of the neocortical areas after neonatal (P7-9) seizures.…”
mentioning
confidence: 99%
“…Thus, rats exposed to neurotoxic compounds during the first few weeks of postnatal development display spontaneous recurrent seizure activity upon reaching adulthood, evident both behaviourally and in electroencephalographic analyses [8], [9]. Exposure to such toxins also provokes the formation of a hyperexcitable hippocampal network in vitro [10], [11]. Similarly, deprivation of maternal care during the first week of life provokes emotional and cognitive behavioural alterations in rodents that are ultimately manifested in adults [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although status epilepticus early in life produces acute changes in terms of metabolic disturbances, it does not necessarily increase the probability to manifest spontaneous seizures later in life (Okada, et al 1984;Stafstrom, et al 1993;Santos, et al 2000;Roch, et al 2002;Raol et al 2003;Kubova, et al 2004;Raffo, et al 2004;Galanopoulou 2008). When spontaneous seizures are recorded, they are few (dos Santos, et al 2000;Raol et al 2003;Kubova et al 2004).…”
Section: Effects Of Early Life Seizures and Status Epilepticusmentioning
confidence: 99%
“…Multiple pilocarpine-induced episodes of status epilepticus in very young rats between 7 and 9 days of age are associated with the development of absence-like epilepsy later on (Ferreira, et al 2003) and these rats show less exploratory activity as well as memory and learning problems (Santos et al 2000). Neuroanatomical studies show no gross pathologic changes but there are progressive, subtle site-specific alterations of intracortical and hippocampal circuitries especially in the expression and the location of GABAergic neurons (da Silva, et al 2005).…”
Section: Effects Of Early Life Seizures and Status Epilepticusmentioning
confidence: 99%